Alternative Questions. Issue 11 (November 2015) - Biezma, María; Rawlins, Kyle
Abstract: This paper surveys the current state of art in research on alternative questions. Alternative questions stand at the confluence of three major topics in semantics, pragmatics, and syntax: questions, disjunction, and intonational meaning/focus. We focus on these components of alternative questions as themes in our survey, arguing for an emerging consensus that (i) disjunction in alternative questions must be modeled in an alternative‐sensitive way, leading to 'non‐classical' treatments where disjunction interacts directly with the semantics and/or pragmatics of questioning (here the debate is about the exact details of this interaction), (ii) to understand alternative questions the interaction of the question structure with intonation and especially focus must be explored, and (iii) a major missing piece in existing work is an exploration of the cross‐linguistic picture. In particular, there are many languages where alternative questions involve a specialized coordinator, which calls into question the uniform treatment of disjunction in alternative questions in general.